The predictive value of the cumulative average for students of the preparatory year for scientific majors at Taibah University by knowing the marks of the general and achievement tests and the average of high school - Solheim, Amro Ahmed; Al-Harbi, Marwan Ali (Journal of Educational and Psychological Sciences, 2022)
The aim of the research was to reveal the predictive value of the cumulative average, and the teacher was represented in studying the degrees of study, achievement, and the high school average, and revealed the structural example that explained the effects, the factor, and the researcher’s use of the descriptive analytical correlative approach. Umm Tamim School, a random sample; It amounted to (300) male and female students in scientific disciplines in the third year, and the analysis was done using the SPSS / AMOS v.21 program. The variance of the research results to the variable in the cumulative ranking among students of the year And that the variable of the general aptitude test did not have a direct effect on the cumulative rate variable among the preparatory year students at Taibah University, which means that there is no direct relationship between the two variables, and that the achievement test variable had a strong direct effect on the cumulative rate variable among the preparatory year students at Taibah University, in reference to the presence of A direct relationship between the two variables with the presence of the median variable (high school average). Based on the results, the researcher presented a number of recommendations and suggestions to take advantage of the predictive tests in determining the appropriate abilities and specializations.